Civil society organizations and managerialism: On the depoliticization of the adaptive management agenda - Gutheil, Lena; Koch, Dirk-Jan (Development Policy Review, 2022)
Motivation In the last decade, a movement formed around making aid del ivery more adaptive, relying on principles such as context sensitivity , flexibility, and ownership. The approaches seem promising for civil society organizations (CSOs) to fulfil their mission of fostering soci al transformation. While several donor agencies have started engaging with such approaches, the authors hardly see their political implicati ons in practice. Purpose The article aims to provide evidence on an ad aptive project and demonstrate how the social transformative and polit ical nature of adaptive development management is rendered technical a nd depoliticized in practice. Methods and approach We use a case study of a development programme based on a social transformative policy fr amework that is implemented through CSOs in Uganda and Vietnam. Data w ere collected by means of interviews, participant observation and docu ment analysis. Findings We find that, in practice, the social transfor mative policy framework is competing with managerial logics. We compar e this process with the depoliticization of the Paris Declaration on A id Effectiveness, finding striking similarities. By using practice the ory, we show how managerialism remains the dominant paradigm in the ci vil society aid sector, fuelling the “anti-politics machine.” Policy i mplications The article shows that policy frameworks do not always wor k as intended. Donors should therefore not only change policy framewor ks, but also start addressing institutional and operational requiremen ts.